Tailoring Permanent Charge Carrier Densities in Epitaxial Graphene on SiC by Functionalization with F4‐TCNQ. Issue 1 (21st October 2022) - Yin, Yefei; Chatterjee, Atasi; Momeni, Davood; Kruskopf, Mattias; Götz, Martin; Wundrack, Stefan; Hohls, Frank; Pierz, Klaus; Schumacher, Hans W.
Abstract: The outstanding properties and the potential for large‐scale fabrication open a wide field for electronic applications of epitaxial graphene on silicon carbide substrates. However, reliable doping methods to permanently control and tailor the carrier concentration to the desired value without applying an electrostatic gate are challenging and still under investigation. In this study, a post‐growth molecular doping technique is investigated that compensates for the high electron density of pristine epitaxial graphene by using the acceptor F4‐TCNQ. By precise adjustment of the dopant concentration, the carrier density can be tuned in a wide range from intrinsic n ‐ to the p ‐type regime. The fabricated quantum Hall devices are ready‐to‐use, and no further treatments are required. High‐precision resistance measurements of graphene‐based devices with different doping levels show a quantization accuracy of 10 −9 that underlines the high quality of the fabricated devices and the suitability of this method for device applications. The experimentally observed correlation between the carrier density and the onset of the quantum Hall plateau gives a reliable criterion for the choice of devices in quantum resistance metrology. Abstract : The electron density of epitaxial graphene on SiC is successfully tuned by adapting the concentration of the molecular dopant F4‐TCNQ in the doping layer atop. Such produced Hall devices are ready‐to‐use and show a correlation between electron density and onset of the quantum Hall plateau in a wide range. This makes the concentration‐dependent doping technique interesting for a wide range of electronic applications e.g., in quantum resistance metrology.